FACE MASK DETECTION AND AUTOMATIC DOOR OPENER USING YOLO. - SAKTHIMANI, S.; HARIKRISHNA, R.; PRAKASH, R. KARTHIK; PIRANESH, S. (Turkish Journal of Physiotherapy Rehabilitation, 2021)
During this COVID-19 pandemic the mask plays a vital role in preventing the people from the spread of the disease. Even before this pandemic some industries like chemical industries, paint industries, cotton industries, etc., Masks are the important thing to prevent the individual life from various diseases. We are currently focusing on the prevention of spread of COVID-19 in public places like ATM's where people didn't wear the mask and spread or being infected by the virus. It's complex task if we use a human power to monitor the individuals in the public as well as high cost too. So, we are providing a solution using the YOLO architecture for facemask detection and also, we are integrating the microcontrollers for automatic opening and closing of doors in the public buildings. In a simple word if an individual wearing a mask means he/she will be allowed to enter otherwise there is an alarm beep sound indicating the absence of face mask. The main objectives of this project are we are ensuring the prevention of virus spread and we can use this project in some industries where the mask is mandatory because of the harmful substance present in the industry, in that case we are preventing the workers from harmful diseases and also helps the organization in the means of cost and care to employee.